Integration of Artificial Intelligence in Character-Based Education: Strengthening Teachers with the Tamansiswa Approach in Indonesian Schools Kota Kinabalu - Ignatius Soni Kurniawan; Umi Wahidah; Suddin Bin Lada; Ana Fitrotun Nisa; Shifa Megarani (International Journal Of Community Service, 2025)
Rapid technological advances, especially in Artificial Intelligence (AI), have brought significant changes to the education sector. This community service program aims to improve the effectiveness of learning at the Kota Kinabalu Indonesian School (SIKK) in Malaysia by integrating AI and anticipating its impact by strengthening character through the Tamansiswa educational philosophy. The method used in this program applies Community-Based Learning (CBL), which encourages active participation in identifying and solving educational challenges. The implementation stages include pre-observation, initial observation, problem formulation, preparation, program implementation, and evaluation. This initiative was carried out through academic collaboration between the University of Malaysia Sabah, Sarjanawiyata Tamansiswa University (UST) Yogyakarta in collaboration with the Consulate General of the Republic of Indonesia (KJRI) Kota Kinabalu, and SIKK to deepen substantial discussions and expand the scope of program implementation. The results of the activity show that the integration of AI in education improves the efficiency of learning at SIKK, while maintaining the values embedded in the Ki Hadjar Dewantara Among System. The output of the activity shows a high level of participant participation. The evaluation noted that the majority of participants felt helped in understanding the application of AI and Tamansiswa in education, while SIKK recommended further development so that the benefits of the program could be sustainable.